The universe. 4 : [videorecording (DVD)] : colonizing space, nebulas, wildest weather in the cosmos - Cohen, Douglas J.; Thompson, Erik, 1959- (A&E Television Networks : Distributed by New Video, 2008)
Venture outside our solar system in another epic exploration of the universe and its mysteries. With strikingly realistic computer re-creations, feel like you have traveled to the edge of the unknown including visiting strange and unfamiliar worlds; prepare for the worst; uncover the secrets of our own galaxy. Learn what 'Dark matter' is and how it takes up 95% of the universe. Find out more about 'White holes,' which actually create matter.